The Effectiveness of Cloud Computing in Developing Saudi-University Students' ‎Writing Skill - Nasr, Mahmoud (Jordan Journal of Educational Sciences, 2021)
The aim of this study was to test the effectiveness of cloud computing in developing the writing skill of Saudi-university students. The participants of the study consisted of (120) students, selected randomly from Al-Qassim University distributed between the experimental and control groups. Both groups were pretested. The experimental-group students were taught by using a proposed model implementing a suggested cloud-computing strategy. The control-group students had their regular writing classes. Then, the posttest was administered. Results indicated that there were statistically significant differences between the mean scores of the two groups on the post test, in favor of the experimental group. However, there were no significant differences between the mean scores of males and females in the experimental group in the post administration of the test